Reciprocity and the values of maqasid sharia among Muslim transmigrant farmers from Java in strengthening agricultural economics - Muharir, Muharir; Hanafi, Syafiq Mahmadah; Soehadha, Moh (Universitas Islam Indonesia, 2025)
IntroductionThe transmigration phenomenon has created new communities in various regions of Indonesia, including the transmigrant Muslim farming community from Central Java in South Sumatra. Facing the social and economic challenges of their new location, these farmers not only utilize their agricultural skills but also develop unique social relationships, such as reciprocity. As Muslims, Islamic values play a crucial role in the lives of farmers, including how they conduct their economic activities. The Maqasid sharia (objectives of sharia) , which encompass the protection of religion ( din ), life ( nafs ), intellect ( aql ), descendants ( nasl ), and property ( mal ), serve as the moral foundation for agricultural activities and social life.ObjectivesThis study aims to examine how transmigrant Muslim farmers from Central Java apply the practice of reciprocity and the values of maqasid sharia in their daily lives, particularly in agriculture.MethodThis study uses a qualitative approach with a reciprocity approach and the values of maqasid sharia . Data collection was conducted through six months of fieldwork using participant observation and in-depth interviews . Interview ). Data analysis used three analysis models: domain analysis, componential analysis, and data analysis with triangulation. This is used to obtain the correct interpretation. Truth is the foundation that a researcher needs to understand.ResultsThe research results show that the practice of reciprocity is an important part of the social and economic life of transmigrant Muslim farmers from Central Java. Some of the most common forms of reciprocity include mutual assistance during planting and harvesting, sharing agricultural produce, and exchanging tools and labor. These methods not only enhance social solidarity but also serve as collective economic strategies to overcome limitations in capital and access to resources. Furthermore, farmers' economic actions and decisions have been indirectly influenced by the principles of maqasid sharia . Thrift, honesty in trade, and fair management of agricultural produce are examples of the value of safeguarding wealth ( hifz). al -mal). The focus on children's education and family welfare shows the principle of protecting the soul and offspring.ImplicationsThe maqasid sharia and reciprocity values helped empower transmigrant Muslim farmers from Java, whose implementation of reciprocity and maqasid sharia values led to improved agricultural economics. While reciprocity creates social solidarity that helps farmers, maqasid sharia ensures economic justice by providing fair distribution of profits and avoiding usury (riba).Originality/NoveltyThis study contributes to the growing literature on Islamic business practices by highlighting the strategies and ethical considerations unique to the Muslim fashion industry. It offers insights into how businesses can balance innovation and tradition to foster sustainable growth.